The Role of Government Health Expenditure In Translating Economic Growth Into Human Development: Dynamic Panel Analysis - Widianto, Hendro Try (Jurnal Anggaran dan Keuangan Negara Indonesia (AKURASI), 2025)
This study addresses the empirical gap in understanding the impact of government health expenditure on the Human Development Index (HDI), particularly across countries with different income levels. Despite the general assumption that economic growth contributes to human development, evidence remains inconclusive regarding the role of government health expenditure in enhancing HDI. To investigate this, the study employs a System Generalized Method of Moments (System GMM) dynamic panel analysis using data from 151 countries over the period 2005–2019, controlling for economic growth, infant mortality rate, government effectiveness, income level, and GDP per capita. This methodology is chosen for its robustness in addressing endogeneity and capturing dynamic relationship in panel data. The results reveal that a one percent increase in government health expenditure as a share of GDP leads to an average increase of 1.07 points in HDI, with the impact significantly stronger in middle-income countries than in high-income countries. These findings highlight the diminishing marginal returns of government health expenditure with rising country’s income level and underscore the importance of allocating sufficient government health expenditure in middle-income countries.